Fault‐tolerant control strategy with reduced switching frequency for inverter‐based fault in open‐winding PMSM system. Issue 11 (1st May 2020) - Lv, Kangfei; Dong, Xiwei; Liu, Lili; Nian, Heng
Abstract : The open‐winding permanent magnet synchronous machine (OW‐PMSM) system is widely investigated for its potential fault tolerance while extra switching loss is inevitable due to the doubled switch devices. Hence, to further improve its performance, a fault‐tolerant control strategy against the inverter‐based fault, in which the corresponding terminal of the phase winding is connected with the mid‐point of the two capacitances in parallel to the dc voltage, is proposed in this Letter. In the proposed method, the reference voltages are modulated under the three‐phase stationary coordinate system, considering the voltage fluctuation of the capacitances. In addition, to reduce the switching frequency, the reference voltages are adjusted synchronously, according to the polarity of the reference voltages. Moreover, the effective modulation range of the proposed method is analysed. Finally, the performance of the proposed strategy is validated experimentally.